2018
DOI: 10.1002/jcaf.22315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ownership Patterns and Firm Life‐Cycle Stages on Firm Performance: Evidence From India

Abstract: This article reexamines the relationship between ownership patterns and firm financial performance through the prism of firm life‐cycle stages. We use an unbalanced panel data set from the S&P BSE 500 companies in the emerging Indian market over nine years. We adopt multivariate analysis with covariance to explore the relationship between ownership patterns and firm performance across various stages of a firm's life cycle. Empirical results suggest that firm life cycle is a key indicator in the study of relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Ownership structure has a significant influence on the governance framework (Kumar and Zattoni, 2016). A study conducted in India and the author stated that agency problem raised in those public companies which don't have concentrated ownership and the mangers make decisions for their self-interest at the expense of shareholder (Sridharan and Joshi, 2018). There are many corporate codes in practice for governing corporations globally.…”
Section: Introductionmentioning
confidence: 99%
“…Ownership structure has a significant influence on the governance framework (Kumar and Zattoni, 2016). A study conducted in India and the author stated that agency problem raised in those public companies which don't have concentrated ownership and the mangers make decisions for their self-interest at the expense of shareholder (Sridharan and Joshi, 2018). There are many corporate codes in practice for governing corporations globally.…”
Section: Introductionmentioning
confidence: 99%
“…During this time frame, a host of organisations had foreign promoters even though their shareholding ranged from 0 to 74%, the mean stakes were closer to 3%. Foreign promoter ownership has been found to positively impact firm performance (Sridharan & Joshi, 2018), while Gu et al (2019) find the evidence to be unclear, especially considering the lack of the underlying rationale. From the developed world, Driffield et al (2018) found the evidence to be inconclusive, hinting at presence of secondary considerations that could effectively link foreign ownership and firm performance.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Thus, we add board size and the percentage of independent directors to all directors as a measure for board independence in our control variables. Following Short (1994) and Sridharan and Joshi (2018), we control for firm age and ownership type (SOE), as life cycle stages and ownership structure are key factors influencing firm performance. Finally, we include commonly used indicators, return on asset, because profitability is one of the determinants of our SGR indicator.…”
Section: Baseline Regression Modelmentioning
confidence: 99%